Connecting Impact and Quality - Prospective Life Cycle Assessment of recycling Carbon Fibre Composites - Gunnarsson, Erik; Kasliwal, Suvidhi (My University, 2024)
This thesis investigates the environmental impacts of recycling possibilities of carbon fibre reinforced polymers (CFRP), for which the intended use is carbon fibre tanks in fuel cell electric vehicles (FCEV’s). The research, conducted in collaboration with Volvo Group Trucks Technology, IVL Swedish Environmental Research Institute and Chalmers, builds on a previous thesis by Weiszflog and Abbas (2022) that aimed to explore and analyse the implementation of different hydrogen storage systems and compare their environmental impacts. This study focuses on identifying and evaluating potential commercial viability of the aforementioned recycling methods for CFRP. Each method’s potential to produce high-quality recycled carbon fibres (rCF) suitable for second-life applications are examined through mechanical quality indicators, e.g. tensile strength, tensile modulus, length and diameter of the recovered fibre. The different recycling systems are later compared in a Life Cycle Assessment (LCA), where the environmental impacts are quantified and compared to one another based on the impact assessment methods climate change, cumulative energy demand, human toxicity, and resource use. One of the primary goals of the thesis is to develop a framework for identifying second-life applications for rCF based on the resulting quality indicators after exiting the recycling processes, as well as complementing and adding onto existing inventory data. The study also analyses an exploratory option for recycling of CFRP, comparing the present with a potential 2030 scenario that considers different electricity mixes and their implications for recycling technologies. Another primary aim for this thesis is to condense the large amount of information available on carbon fibre recycling and its resulting mechanical quality into a table that can be used in future assessments. The thesis also aims to act as inventory data for future work related to CFRP recycling. The research concludes that effective recycling of CFRP can significantly reduce the environmental impacts associated with the material’s production and disposal. By implementing improved recycling technologies, either the same industry or neighboring industries, such as nautical or personal vehicles, can use the rCF instead of virgin carbon fibre (vCF), and through the usage make substantial strides towards decarbonisation and addressing the exponentially growing demand for carbon fibres.
Keywords: Life Cycle Assessment; Carbon Fibre Reinforced Polymers; Hydrogen Storage; Quality Indicators; Thermal Recycling; Mechanical Recycling; Chemical Recycling; Second-Life Applications; Mechanical Properties; Second-Life applications